2014
DOI: 10.7150/jca.8486
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Serum Level of Lymphatic Vessel Endothelial Hyaluronan Receptor-1 and Prognosis in Patients with Lung Cancer

Abstract: Background: Lymphatic vessel endothelial hyaluronan receptor-1 (LYVE-1) is a hyaluronic acid receptor that is selectively expressed in the endothelia of lymphatic capillaries. The density of lymphatic vessels expressing LYVE-1 on immunohistochemistry negatively correlates with prognosis of patients with non-small-cell lung cancer. However, the relationship between LYVE-1 serum levels and lung cancer staging is unknown.Methods: We collected blood samples from 58 lung cancer patients before treatment and measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 38 publications
0
30
0
Order By: Relevance
“…With the influence of various environment, the morbidity and mortality of lung cancer have been growing fast in recent years.Lung cancer threatens people's health and the quality of human life (Nunomiya et al, 2014). Hyper-methylation of promoter region of tumor suppressor genes occurs, so that the gene silencing, and increase the risk of cancer (Shicheng et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…With the influence of various environment, the morbidity and mortality of lung cancer have been growing fast in recent years.Lung cancer threatens people's health and the quality of human life (Nunomiya et al, 2014). Hyper-methylation of promoter region of tumor suppressor genes occurs, so that the gene silencing, and increase the risk of cancer (Shicheng et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Interactions between LYVE-1 and the extracellular matrix glycosaminoglycan, HA, may regulate leukocyte migration through the lymphatic vasculature ( 38 ). The serum level of LYVE-1 has been identified to be significantly lower in patients with lung cancer with metastasis in comparison with those without ( 6 ). It has been suggested that LYVE-1 could be used in predicting cancer progression ( 6 ).…”
Section: Lyve-1mentioning
confidence: 99%
“…The serum level of LYVE-1 has been identified to be significantly lower in patients with lung cancer with metastasis in comparison with those without ( 6 ). It has been suggested that LYVE-1 could be used in predicting cancer progression ( 6 ). The interaction between LYVE-1 and HA was identified to be involved in the adhesion of tumor cells to lymphatic vessels ( 39 ).…”
Section: Lyve-1mentioning
confidence: 99%
“…However, some studies have claimed that high LVD may be a marker for good prognosis. The study by Nunomiya and colleagues showed that lung cancer patients with lower LYVE-1 levels have poorer prognoses than patients with higher LYVE-1 levels [ 25 ]. Yang and his team demonstrated the role of the epigenetic regulation of desmoplakin in increasing the sensitivity of cancer cells to anticancer drug-induced apoptosis, implying the clinical value of desmoplakin for the treatment of patients with lung cancer [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Desmoplakin, also known as desmosome-related transmembrane protein, is a desmosomal protein expressed at intercellular junctions. Some studies have shown that lymphatic endothelium markers can be used to predict poor prognoses in NSCLC patients [ 22 24 ], but other studies have refuted this view [ 25 27 ]. Therefore, whether LVD is a prognostic biomarker for the survival of NSCLC patients remains controversial.…”
Section: Introductionmentioning
confidence: 99%